Exploring the Role of TED Talks in Developing EFL College Students' Critical Listening Skills - Yuni Permata sari; Maisa; Farah Sukmawati Wahidah (Al-Qalam Institue, 2026)
This study aimed to explore how TED Talks contribute to the development of EFL college students' critical listening skills by examining their learning experiences and perceptions of analyzing, interpreting, and evaluating authentic spoken English. A qualitative descriptive design was employed involving 26 undergraduate English Education students at an Indonesian university. Data were collected through Likert-scale and open-ended questionnaires, followed by semi-structured interviews with five purposively selected participants. The data were analyzed using Miles, Huberman, and Saldaña's interactive model supported by descriptive statistics. The findings revealed four interconnected themes: TED Talks promoted analytical listening by improving students' ability to identify main ideas and discourse organization; enhanced interpretation of spoken messages through contextual reasoning and repeated listening; encouraged critical evaluation by examining arguments and supporting evidence; and fostered self-regulated learning through strategic use of subtitles, replaying videos, and vocabulary searches. Overall, TED Talks functioned as authentic digital learning resources that strengthened critical listening and learner autonomy. These findings imply that integrating TED Talks into EFL listening instruction can effectively promote higher-order thinking and independent learning.